ChemInform Abstract: Synthesis of Magnetically Recyclable ZIF‐8@SiO2@Fe3O4 Catalysts and Their Catalytic Performance for Knoevenagel Reaction. Issue 14 (April 2015) - Li, Qingyuan; Jiang, Sai; Ji, Shengfu; Ammar, Muhammad; Zhang, Qingmin; Yan, Junlei
Abstract: The title catalyst is prepared by addition of aqueous 2‐methyl imidazole solution containing NEt3 to an aqueous suspension of Zn(NO3 )2 and SiO2 @Fe3 O4 .